Performance evaluation of ethanol-derived waste cooking oil biodiesel in a forced-draft commercial burner system - Ma. Leona Maye B. Pepito; Jasper V. Acierto; Katrina Mae S. Raiz; Lance Erroyl J. Sambaan; Alyssa Mae S. Tabasa (Researcher and Lecturer Society, 2026)
The improper disposal of waste cooking oil (WCO) presents significant environmental challenges, yet its potential as a renewable fuel remains underutilized. This study optimized the conversion of WCO into biodiesel through a two-step esterification and transesterification process and evaluated its performance in a commercial burner system compared to liquefied petroleum gas (LPG). The process employed acid-catalyzed esterification followed by alkaline transesterification using ethanol and potassium hydroxide, with ethanol-to-oil molar ratios of 11:1, 12:1, and 13:1. The 13:1 ratio was identified as optimal, yielding 165.85 g of crude biodiesel per 100 g of oil with reduced glycerol formation. Physicochemical characterization revealed a flash point of 160°C and a calorific value of 35.65 MJ/kg, satisfying key ASTM D6751 requirements. However, the density of 0.9756 g/mL exceeded the standard range, suggesting the presence of residual ethanol and the need for improved post-treatment purification. Performance testing showed that the biodiesel-fueled burner heated 1 L of water in 381.33 s, compared to 420.67 s for LPG, demonstrating enhanced heating performance. The system achieved a thermal efficiency of 19.46% and a specific fuel consumption of 1.48 MJ/L. Emission analysis confirmed complete combustion, with carbon monoxide levels of 22.3 ppm and zero hydrocarbon emissions. The improved performance is attributed to the use of a forced-draft burner system, which enhances fuel atomization and combustion stability. Overall, the results demonstrate that transesterified WCO is a viable and cleaner alternative to conventional fossil fuels, offering a practical waste-to-energy solution for small-scale commercial cooking applications.